KOMUNIKACYJNE FUNKCJE TWITTERA. UŻYTKOWNICY SERWISU MIKROBLOGOWEGO WOBEC SYTUACJI ZAGROŻENIA NA PRZYKŁADZIE SERII ZAMACHÓW TERRORYSTYCZNYCH W PARYŻU - Mołodziejko, Justyna (Civitas et Lex, 2017)
The presented paper concerns information and communication functions of the microblog Twitter during and after terrorist attacks in Paris in 2015. The main purpose of this publication is to point out functions of content described with such hashtags as: #porteouverte, #rechercheparis, #prayforParis, #wearenotafraid, #noussommesunis. Twitter’s users used listed hashtags mainly to: 1) send people (who were in the area of terrorist attacks) information on where they can find safe place to stay, 2) look for lost people more effectively, 3) show support to people touched by the tragedy. On the November 13th 2015 and a few days after series of terrorist attacks in Paris Twitter was an important communication space, the place of giving help and support in fight with terrorism.